Multinational firms' organisational dynamics: Competition intensity and the ownership decision under uncertainty - Leandro Navarro (ZBW - Leibniz Information Centre for Economics, 2021)
I analyse firms organisational choices when they face uncertainty about institutional conditions in foreign locations with heterogeneous final good producers and incomplete contracts. As firms learn about the conditions abroad, the increasing offshoring activity increases competition in the final goods market, leading to a progressive vertical disintegration of the supply chains. Initially, the firms that decide to explore offshoring potential choose integration. As competition in final good markets intensifies, the least productive ones among them switch sequentially to arm's length trade. In the fully domestic supply chains, the increasing competition promotes a sequential disintegration of the domestic intermediate input suppliers. I test for the predictions of the model using sectorallevel data for the US manufacturing sectors.
Keywords: D21; D23; D81; D83; F14; F21; F23; L22; 330; Firm theory; multinational firms; incomplete contracts; global sourcing; uncertainty; sequential offshoring; information externalities; learning; competition; outsourcing; forward and backward integration; FDI